The Benefits of Fasting to Improve Health Conditions and to Prevent Cardiovascular Disease - Wahyu Sukma Samudera; Gracia Victoria Fernandez; Rahmatul Fitriyah; Hidayat Arifin; Shenda Maulina Wulandari; Roby Aji Permana (Universitas Airlangga, 2019)
Introduction: Fasting is defined as the voluntary abstinence from eating for variable time intervals and it has been associated with potential beneficial impacts on human health. The study was to review the benefits of fasting on cardiovascular health in humans with or without cardiovascular disease.Methods: The databases search was done using the keywords ‘fasting’ and ‘cardiovascular system’ using Scopus, Science Direct and ProQuest, limited to between 2013 and 2019 for publication year. A total of 3.619 articles were obtained and 15 articles involving experimental and non-experimental studies were used as the reference material.Results: The findings showed that in people who are healthy, fasting can reduce the inflammatory markers (IL-1 & IL-6, TNF-α), the oxidative stress marker (Malondialdehyde), body weight, abdominal circumference, fasting blood glucose, LDL, triglyceride and blood pressure. In people at risk or with cardiovascular disease, fasting can reduce body weight, body mass index, abdominal circumference, fat percentage, blood pressure, triglyceride, the biomarker of inflammation (serum amyloid A), the biomarker of oxidative stress (protein carbonyl), the biomarker of endothelial dysfunction (asymmetric dimethylarginine) and increase the vascular endothelial growth factor.Conclusion: Based on these findings, fasting can improve the health condition of people at risk or with cardiovascular disease by improving the risk factors such as blood pressure, overweight and endothelial dysfunction. In people who are healthy, fasting can be used for the prevention of cardiovascular disease by helping to maintain their weight, blood pressure, LDL and triglyceride within the normal limits.